Lepa and Trickle Irrigation of Cotton in the Southeast Anatolia Project (GAP) Area in Turkey - Yazar A.; Sezen S.M.; Sesveren S. (Annual Meeting of the Mediterranean Network on Collective Irrigation Systems (CIS_Net), 2000)
Low Energy Precision Application (LEPA) is a self-moving circular or linear irrigation system that applies water at or near the soil surface. The primary purpose of LEPA is to efficiently apply irrigation water for the production of crops and forage in an energy efficient manner (Lyle and Bordovsky, 1981). The present study was conducted at the Koruklu Research Station of the Scientific and Technical Research Council of Turkey (TUBITAK) in the Sanliurfa Province in Southeast Anatolia Project (GAP) area during 1999. Trickle and LEPA irrigation of cotton in GAP region of Turkey were found to be comparable to other irrigation methods such as sprinkler and furrow. Deficit LEPA and trickle irrigation of cotton generally reduced seed cotton yield. Both trickle and LEPA systems permitted precise control of the irrigation applications and provided uniform irrigations.
Proceedings of the Annual Meeting of the Mediterranean Network on Collective Irrigation Systems (CIS_Net), 1999/11/03-06, [sl] (Malta)